Faktor-faktor yang mempengaruhi jumlah kelahiran - Lestari, Dinny Fitri Indah; Musa, Adnan Haris; Roy, Juliansyah (Faculty of Economics and Business Mulawarman University, 2018)
The aims of this research are to know and explain the factors-factors that affect fertility (family income, wife education level, age of first marriage, and use of contraception) effect significantly to the amount of fertility in the Village of Rapak Dalam. This research used primary data i.e data obtained directly from the respondents. Data analysis using multiple linear regression with dummy variable model with SPSS software (Statistical Program for Social Science) Version 20. Research result showed: (1) family income influential variables are positive and significant against the amount of fertility in the village of Rapak Dalam; (2) wife education level variable is negative and significant effect against the amount of fertility in the village of Rapak Dalam; (3) age of first marriage variable is negative and significant effect against the amount of fertility in the village of Rapak Dalam; (4) use of contraception variable is negative and insignificant effect against the amount of fertility in the village of Rapak DalamKeywords : family income, wife education level, age of first marriage, and use of contraception